Objectivity, Social Sciences, and the Charge of Inferiority - Adeyanju, Olanshile Muideen (Conatus - Journal of Philosophy, 2023)
This paper challenges the charge of inferiority, on the basis of objectivity, against the social sciences. The idea of objectivity is that facts about the state of the world and entities in it are observed or studied without a taint of personal bias, value judgement or particular perspective. The social sciences are accused of falling short of the requirements of objectivity hence they are considered inferior to the natural sciences which are claimed to merit the requirements. This paper argues that the idea of objectivity has been misleadingly conceived as a method exclusive only to the natural sciences. The paper maintains that if the concept of objectivity is conceptually analysed and conceived in a strict sense, the ideals and requirements of objectivity would be outside the ken of both the natural sciences and the social sciences. However, if the concept of objectivity is conceived in a moderate sense, the social sciences would merit being called objective as much as the natural sciences. Thus, a conceptual analysis will show that both the natural sciences and social sciences are at par on the threshold of objectivity. Thus, the paper submits that the social sciences are not inferior to the natural sciences on the basis of objectivity.